Older Women’s Experiences in the Icelandic Workforce – Positive or Negative? - Sigurðardóttir, Sigurveig H.; Snorradóttir, Ásta (Nordic Journal of Working Life Studies, 2020)
The purpose of the study is to gain a deeper understanding of older women’s experiences in the labour market, how they value their job opportunities and perceived attitudes towards them. Qualitative interviews were conducted with seven women aged 57–74 years who all have at least 10 years working experience after they turned 40. Experiencing discrimination in the workforce was often mentioned by the women. Their experience is that men are less discriminated against on grounds of age than women. Older women pride themselves for participating in the workforce for being reliable, unselfish and undemanding rather than being experienced, skillful and good at their jobs. The results indicate that it is important to research further the well-being of older women in the labour market and try to change the negative attitudes and discrimination that appear prevalent. Ageism against older women can affect their well-being and health and must be prevented.